Implementing the 7-1-7 target to improve epidemic preparedness and response in Uganda - Francis Kakooza; Mohammed Lamorde; Godfrey Bwire; Elizabeth Mgamb; Christopher Lee; Maureen Nyonyintono; Issa Makumbi; Aaron F Bochner; Yonas Tegegn Woldemariam; Allan Muruta; Lydia Nakiire; Joshua Kayiwa; et al. (BMJ Global Health, 2025)
Early and effective response actions are vital to mitigate outbreaks and other public health events. The 7-1-7 target (7 days to detect, 1 day to notify and 7 days to complete early response actions) is a performance improvement approach for epidemic preparedness. 7-1-7 data were collected by rapid response teams and presented to stakeholders at National Task Force (NTF) meetings, Uganda’s primary outbreak coordination platform, in the days immediately after event detection. From October 2021 to December 2022, 7-1-7 data were collected for 13 ongoing events that were presented at NTF meetings as well as 29 lower-risk events for which the NTF was not convened. Among these 42 events, 22 (52%) met the 7-day detection target, 31 (74%) met the 1-day notification target and 19 (45%) met the 7-day early response target, with 10 (24%) meeting all 7-1-7 target components. Systems bottlenecks identified across the 42 events were consolidated, shared with stakeholders and integrated into Uganda’s National Action Plan for Health Security (NAPHS) Operational Plan. Of the 108 subactivities in the 2023 NAPHS Operational Plan, 17% aligned with recommended activities that emerged from 7-1-7 implementation. Uganda’s experience demonstrated that real-time 7-1-7 reviews improved ongoing public health responses and that synthesising 7-1-7 data across events identified recurrent systems bottlenecks that warranted prioritisation during NAPHS operational planning. We recommend that other countries adopt WHO’s 2023 guidance on incorporating the 7-1-7 approach into Early Action Reviews to improve their outbreak responses.